2001
DOI: 10.1081/jas-100000262
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Peak Expiratory Flow Rates in Cork Workers' Occupational Asthma

Abstract: Suberosis is an occupational lung disorder of cork industry workers usually presenting as an extrinsic allergic alveolitis, but airway involvement in some cases makes the diagnostic approach complex. We assessed peak expiratory flow rates (PEF) in 17 cork workers with asthma symptoms that worsened at work, comparing three methods of PEF graph analysis. Complete agreement (three observers) was found in 12 of 17 cases (70.6%) with the visual inspection of mean daily values and in 11 of 17 cases (64.7%) with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Traditionally, as in other occupational settings such as those of bird fanciers and farmers, this exposure leads to the development of hypersensitivity pneumonitis. However, description of cases of asthma in these settings is now more common, and its aetiology needs some clarification (Arlian et al 1997;Colloff et al 1997;Winck et al 2001;Hirakata et al 2002). In the absence of an identifiable aetiological agent, the assessment of peak expiratory flow rates, at and away from work, is a valuable diagnostic method to ascertain the occupational nature of a worker's asthma (Winck et al 2001).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Traditionally, as in other occupational settings such as those of bird fanciers and farmers, this exposure leads to the development of hypersensitivity pneumonitis. However, description of cases of asthma in these settings is now more common, and its aetiology needs some clarification (Arlian et al 1997;Colloff et al 1997;Winck et al 2001;Hirakata et al 2002). In the absence of an identifiable aetiological agent, the assessment of peak expiratory flow rates, at and away from work, is a valuable diagnostic method to ascertain the occupational nature of a worker's asthma (Winck et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…However, description of cases of asthma in these settings is now more common, and its aetiology needs some clarification (Arlian et al 1997;Colloff et al 1997;Winck et al 2001;Hirakata et al 2002). In the absence of an identifiable aetiological agent, the assessment of peak expiratory flow rates, at and away from work, is a valuable diagnostic method to ascertain the occupational nature of a worker's asthma (Winck et al 2001). Accordingly, we have shown that the visual analysis of the mean, maximum, and minimum daily PEF values may be the procedure of choice to support the occupational nature of asthma in the cork industry.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A study by Wink et al (22) showed that mean peak fl ow in workers decreased on the day of exposure and increased on days when the workers were away from work. In our study, the mean peak fl ow at the end of the shift on the day of painting was signifi cantly lower than at the start of the shift, which may be related to HDI exposure.…”
Section: Discussionmentioning
confidence: 99%